The behaviour and performance of metal oxide varistor under the application of multiple lightning impulses - Yaacob, Mohd. Muhridza (2005)
The behaviour and performance of lightning protective devices such as the metal oxide varistor (MOV) under the application of multiple lightning impulse are different from that of the standard single stroke test. Since the MOV is the most common, economical and reliable device for low voltage and telecommunication systems lightning protection, a precise method of testing has to be adopted based on natural characteristics of lightning to accurately determine its performance and capability. In this work, a Multiple Lightning Impulse Generator (MIGe) with new electronic delay triggering technique with a voltage capability of 5 kV and a current capability of 1 kA has been designed, constructed and developed in the laboratory to conduct impulse testing based on natural lightning parameters. The generator can produce up to five sequences of impulse voltage and current with variable characteristics such as impulse waveshapes and time interval between impulses. This system also incorporates an electronic triggering and delay circuit to initiate and delay the breakdown process of the sphere gaps. Laboratory studies are then being carried out on 2 kV and 5 kV voltage and 1 kA current ratings metal oxide varistors. The electrical and thermal responses of the device are then being analyzed to determine the effect on the varistor characteristics. From the results it has been found that material degradation has occurred on the MOV test samples when multiple lightning impulse are being subjected as compared to the standard testing procedures. The degradation is shown by reduction in the electrical characteristics where the DC voltage at 1 mA current value reduces more than the tolerable limits of Â±10%. The other parameters being studied which are the temperature, insulation resistance, capacitance and partial discharge also showed a considerable effect whereby the percentage change is significant when the multiple impulse is applied.